Giant Choroid plexus papilloma in a child: A Case Report - Joshi, Sumit; Sharma, Gopal R; Bhattachan, Maya (Nepal Journal of Neuroscience, 2016)
Tumors of the choroid plexus are rare neoplasms of neuroectodermal origin, accounting for less than 1% of all intracranial tumors. We report a case of giant choroid plexus papilloma of the lateral ventricle extending into the third ventricle of a 3 years old female child. She presented with features of obstructive hydrocephalus and had undergone V-P shunt at the age 3months. She repeatedly underwent revision of the V-P shunt at the age of 6 months, 22 months and 36 months prior to the tumor excision. An anterior interhemispheric, transcallosal approach was performed and total excision was achieved with fenestration of lamina terminalis at the age of 37 months. Following the surgery the patient developed bilateral subdural effusion requiring bilateral subdural-peritoneal shunt and the nonfunctional V-P shunt was removed. Histological evaluation confirmed the diagnosis of the choroid plexus papilloma. Nepal Journal of Neuroscience 13:57-59, 2016